Pengaruh Medium Kultur Bebas Serum terhadap Perkembangan Preimplantasi Embrio Mencit in vitro - Eriani, Kartini; Sunarti, Sunarti; Nasir, M.; Djuwita, I. (Lembaga Penelitian Universitas YARSI, 2008)
The use of serum in a culture medium is a common practice in the study of mouse embryo development in vitro. However, the role of unknown factors in serum influencing the embryo development has been difficult to determine. The aim of this study was to investigate the effect of amino acid in serum free medium on in vitro development of mouse embryo. This study was conducted in the following ways: (1) medium M16 supplemented with 0.3% BSA, (2) medium M16 supplemented with 2% v/v MEM, and (3) medium M16 supplemented with 2% v/v MEM and 0.1 mmol of glutamine. The embryos were collected in 3 stage of development: zygote (day-1), morula (day-3) and compacted morola (day-4). The results indicated that supplementation of amino acid into M16 culture medium could replace the role of BSA aims at supporting the developmental potency of mouse embryos in vitro.